Modelling of Most Adaptive Early Warning System Againts Dam Failure Applying Geo-Hydrotechnical Approach - Legono, Djoko; Fathani, Teuku Faisal; Rahardjo, Adam Pamudji; Prabowo, Irawan Eko; Fujita, M (2010)
The dam development requires sufficient factor of safety failure, where in some extent, over topping condition is totally not supposed to take place at any situation. a considerably high attention should be paid not only during the survey, investigation and construction, but also within the period of operation and maintenance. The Indonesian new system of decentralization apparently needs to be anticipated in such a way that the dam management is simple but meets the optimum beneficiary.One hand, optimum beneficiary means economically feasible, in the other hand, means acceptable. Accountability of the dam management is therefore need to be made available, and the continuous evaluation need to be carried out thoroughly. This paper evaluates the catastrophic disaster of Situ Gintung Dam ("Situ" is the local term for a natural small reservoir) disaster which occurred at March 27, 2009. Since there is only little information. due to the size of the dam is relatively small, evaluation id carried out utilizing data obtained from historical record as well as field survey (confirmation with government institutions as well as local community). Hydraulics and hydrology and its tributary where Situ Gintung Dam is located. The dam break phenomenon which produces discharge pulse is also presented to examine the initial flow hydrograph which causes debris flow downstream of the dam. The geotechnics analysis involves the mechanism of the dam failure as the results of the rapid increase in reservoir water level followed by the decrease in soil strength parameter. Result of analysis highlight the understanding that unless sufficient and reliable data is available. both over topping and/or breaching still be possible to cause the catastrophic disaster. Geotechnical analysis applying soil condition data at the surrounding Situ Gintung area indicates that interaction between the dynamic of water surface elevation and the earth fill dam plays significant role in the occurrence of Situ Gintung dam failure. The Appurtenances of Situ Gintung (Irrigation gates, spillway structures, spillway gates, etc) as well as the additional facilities such a jogging track, were evaluated to understand the historical aim of the dam development. Recommendations are presented in respect with the necessary monitoring techniques in hydraulics-hydrology and geotechnical parameters, which is aimed at reducing risk due to similiar disaster.